2022
DOI: 10.1177/10778012221099986
|View full text |Cite
|
Sign up to set email alerts
|

Women Survivors of Adolescent Dating Violence Describe the Maintenance of Their Abusive Relationships: First Person Stories via YouTube

Abstract: The current study explores the personal stories of young women on their own experiences with adolescent dating violence and focuses on their perceptions of the relevant factors that maintained the relationship over time. To this end, we analyzed seven publicly available videos on YouTube of women explaining their experiences of adolescent dating violence, including how they perceived their relationships to be maintained over time. We identified four major sources these survivors perceived as contributing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Storytime styles, in contrast, lend the viewer insight into the more private aspects of the vlogger’s experience with pain. The storytime genre has been described as videos wherein the YouTuber sits in their home and speaks directly to the camera as if having a conversation with the viewer ( Hegel et al, 2022 ). Here, this style is characterized by a handheld camera and a lack of video editing effects, contributing to a more raw and authentic feeling video that simulates a personal video call.…”
Section: Results Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Storytime styles, in contrast, lend the viewer insight into the more private aspects of the vlogger’s experience with pain. The storytime genre has been described as videos wherein the YouTuber sits in their home and speaks directly to the camera as if having a conversation with the viewer ( Hegel et al, 2022 ). Here, this style is characterized by a handheld camera and a lack of video editing effects, contributing to a more raw and authentic feeling video that simulates a personal video call.…”
Section: Results Of Analysismentioning
confidence: 99%
“…By transcribing and coding visual content alongside the speech, we analyzed the themes vloggers discussed as well as the meaningful composition of the videos to lend insight to how they contextualized menstrual pain. Analysis of the video settings and scenes found that vloggers weave throughout “storytime” ( Hegel et al, 2022 ) and documentary styles to pull a taboo and private topic into the more public sphere of information sharing and knowledge transmission. The storytelling style that mimics a one-on-one conversation grounds the intimate subject matter in a popular genre, while vloggers additionally use more public settings, editing techniques, and audio–video effects to create educational content and transmit knowledge that goes beyond the scope of their personal experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, videos chosen were in the vlog style, as commonly used by influencers to show day to day activities. In contrast, a study by Hegel et al (2022) investigated how adolescents describe their experiences with abusive relationships on YouTube. These researchers chose videos that used a Storytime format (i.e., monologues about a specific life event told as though having a one-on-one conversation with the viewer) because the format was more frequently used for discussion of intimate topics.…”
Section: Sampling Considerationsmentioning
confidence: 99%
“…Without adequate analytical methods, researchers might focus on one source and ignore the other. For example, in our lab’s recent analysis of how young women who have experienced adolescent intimate partner abuse describe the maintenance of their abusive relationships, we described the characteristics of the YouTube method used (i.e., “storytime”; Hegel et al, 2022, p. 820) but only analyzed the YouTubers’ spoken dialogue (Hegel et al, 2022). We sought to address this limitation in our future work, which led to the development of our Four Column Analysis Structure (FoCAS) described here.…”
Section: Introductionmentioning
confidence: 99%